Modeling G2g Usage Among Government Employees In Kuwait: The Contingent Role Of User Monitoring, User Resistance, And Task Interdependence - Almutairi, Faisal L F H (2022)
In 2017, The Kuwait government implemented the G2G system in government ministries to support the achievement of the 2035 Kuwaiti vision and to overcome the delay of the government transactions done by employees. The new Kuwait vision 2035 consists of many goals to be achieved, and the most important goal is to make Kuwait a financial and commercial center by improving the government online services provided by employees. Despite the continuous development that the Kuwaiti government made to the e-government system, government transactions were still delayed by employees. Therefore, this research focused on identifying factors affecting the performance of employees using G2G system in Kuwait ministries. DeLone and McLean (2003) was utilized in this research to determine the employee’s performance in Kuwait ministries, and fifteen hypothesizes were developed based on the model developed. The model also has been extended in this study by adding task interdependence, user monitoring, user resistance, and user training to the original model. pre-test was conducted in this study with a number of academic experts, field experts, and respondents to fully comprehend the underlying concept. Survey was used as the research instrument and the unit of analysis is employees using G2G system in Kuwait ministries, and 290 respondents were obtained out of 500 printed hardcopy questionnaires distributed in 5 ministries (consisting of 73% users of all state ministries). The data obtained from the survey was analyzed using Partial Least Square (PLS-SEM).